Ferrocenyl Alkylammonium N-Substituted Polypyrrole Containing Pt and Pd and Its Application on Electroanalysis of Arsenite - Sanchez-Poblete, J (Sociedad Chilena de Quimica, 2016)
Arsenic occurs in a variety of forms and oxidation states and is a very toxic element. The main inorganic arsenic species present in natural waters are arsenate (oxidation state V) and arsenite ions (oxidation state III). Arsenite is more toxic and mobile than arsenate. Therefore, it is important the development of new materials for analysis and control of these toxic species. This research proves that polymer-metal composite electrode materials synthesized by incorporation of Pt0 and Pd0 nanoparticles into a poly(pyrrole-ferrocenyl alkylammonium) matrix present electrocatalytic properties towards the oxidation of arsenite to arsenate. The polymer films displayed a stable electrochemical response in aqueous solution. However, when the polymer film modified electrode were transferred to aqueous solution in presence of arsenite anions, the CV curves for polymer films were deeply modified by the decrease in the electroactivity of the film. It can be concluded that the cationic polymer films present a strong affinity toward arsenite anions. The composite films containing Pt0 or Pd0 showed catalytic activity towards oxidation of As(III) to As(V) due to the presence of metal catalyst particles into the polymer films.